PENGARUH KOMUNIKASI INTERPERSONAL DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PT. SELATAN PRIMA SEJAHTERA JAYA PEKANBARU - Johanes, Johanes; Indarti, Sri; Restu, Restu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine the effect of partial and simultaneous interpersonal communication and organizational climate simultaneously on the performance of employees of PT. South Prima Sejahtera Jaya Pekanbaru. The sample in this study were all employees of PT. South PrimaSejahtera Jaya Pekanbaru totaling 35 people. The technique of collecting data using questionnaires. Data analysis technique is quantitative descriptive method and regression.The results showed that interpersonal communication variables (X1) partially no effect on the performance of employees, organizational climate variables (X2) partially affect the performance and interpersonal communication variables (X1) and organizational climate variables (X2) simultaneously affect the performance of employees of PT. Selatan Prima Sejahtera Jaya Pekanbaru.Companies are advised to keep their employees working organizational climate in a way to keep the working atmosphere is created in a conducive environment so that employees will feel happier in their daily work. Working atmosphere needs to be maintained is the working atmosphere among employees andbetween employees and management.Keywords : Interpersonal Communication, Organizational Climate, Performance.